Effects of processing parameters on the leakage current of silicone rubber insulator - Nazir Ali, Nornazurah; Zainuddin, Hidayat; Abd Razak, Jeefferie; Abd-Rahman, Rahisham; Ambo, Nur Farhani (Institute of Advanced Engineering and Science, 2024)
Silicone rubber (SiR) is known for its exceptional electrical insulation properties. The performance of SiR could be affected by many factors, including processing parameters, particularly mixing speed and time. While these parameters are crucial for ensuring the homogeneity of blended polymeric materials, their electrical impact remains relatively unexplored. This research investigates the effect of varying processing parameters on SiR samples during rapid aging under the incline plane tracking (IPT) test. The study unfolds in three phases, with the final IPT stage revealing the significant influence of different mixing speeds and times on the recorded leakage current (LC) values for each sample. Sample 2, subjected to 70 rpm mixing speed and 10 minutes of mixing time, exhibited great resistance to tracking and erosion. Fourier transform infrared spectroscopy (FTIR) was conducted on the samples before and after the IPT test to further analyze the impact of the varying processing parameters. Once again, sample 2 displayed notable resilience, demonstrating lower reductions in absorbance values for key functional groups. In conclusion, the specific processing parameters of 70 rpm and 10 minutes have been shown to positively influence the performance of SiR, enhancing their resistance to tracking and erosion during rapid aging.